Conducting Materials Based on Epoxy/Graphene Nanoplatelet Composites With Microwave Absorbing Properties: Effect of the Processing Conditions and Ionic Liquid - Silva, Adriana A.; Stein, Raiany; Campos, Daniela; Indrusiak, Tamara; Soares, Bluma G.; Barra, Guilherme M. O. (Frontiers in Materials, 2019)
Conducting composite materials based on epoxy matrix loaded with graphene nanoplatelets (GNP) were prepared by different procedures using ultrasonication. The dispersions of GNP in a mixture of epoxy/methyl-tetrahydrophthalic anhydride without solvent, resulted in composites with better conductivity, higher storage modulus and higher glass transition temperature than those prepared with solvent assisted procedure, indicating better filler dispersion. The non covalent functionalization of GNP with the ionic liquid, 1-butyl-3-methyl-imidazolium bis(trifluorosulfonyl) imide (bmim.TFSI) contributed for an increase of the modulus for the systems containing low amount of filler. The electrical conductivity was not influenced by the presence of ionic liquid. Nevertheless, the micro-wave absorption effectiveness in the frequency range of 8-12 GHz (X-band frequency) was improved by the presence of IL mainly for the composites containing 0.9 and 1.5 vol.% of filler. All systems were characterized by low viscosity, comparable to that of neat epoxy resin, thus making easier their application on the development of coatings, conducting adhesives, etc.